2014
DOI: 10.1038/modpathol.2013.125
|View full text |Cite
|
Sign up to set email alerts
|

CCND1/CyclinD1 status in metastasizing bladder cancer: a prognosticator and predictor of chemotherapeutic response

Abstract: The CCND1 gene encodes the protein CyclinD1, which is an important promoter of the cell cycle and a prognostic and predictive factor in different cancers. CCND1 is amplified to a substantial proportion in various tumors, and this may contribute to CyclinD1 overexpression. In bladder cancer, information about the clinical relevance of CCND1/CyclinD1 alterations is limited. In the present study, amplification status of CCND1 and expression of CyclinD1 were evaluated by fluorescence in situ hybridization and immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 42 publications
3
54
0
Order By: Relevance
“…Abnormal expression of CCND1 has been reported in a variety of human tumors, including breast cancer [18,19], bladder cancer [20,21], colon cancer [22,23], and glioma also included [24,25]. Growing evidence demonstrated that CCND1 is a potential therapeutic target in cancer [26,27]. In this study, we identified that CCND1 was up-regulated in glioma tissues, and found that the increased miR-383 level in glioma cells resulted in down-regulation of CCND1 protein expression.…”
Section: Discussionmentioning
confidence: 66%
“…Abnormal expression of CCND1 has been reported in a variety of human tumors, including breast cancer [18,19], bladder cancer [20,21], colon cancer [22,23], and glioma also included [24,25]. Growing evidence demonstrated that CCND1 is a potential therapeutic target in cancer [26,27]. In this study, we identified that CCND1 was up-regulated in glioma tissues, and found that the increased miR-383 level in glioma cells resulted in down-regulation of CCND1 protein expression.…”
Section: Discussionmentioning
confidence: 66%
“…In the present study, we demonstrated that the cyclin D1 LI was consistently higher than the Ki-67 LI. Cyclin D1 is associated with oncogenesis of various types of tumors, including mantle cell lymphoma [24], breast cancer [25], esophageal carcinoma [26], endometrioid carcinoma [27], gastric carcinoma [28], bladder cancer [29], and cholesteatoma [30]. In brain tumors, the expression of cyclin D1 has been reported in medulloblastomas [31].…”
Section: Discussionmentioning
confidence: 98%
“…Cyclin D1 is a gene that controls the cell cycle and promotes cell cycle progression through G1-phase by forming active holoenzymes with cyclin-dependent kinase (CDK)4 and CDK6, which leads to phosphorylation of retinoblastoma protein (28). Cyclin D1 overexpression has been demonstrated to be an independent adverse risk factor in metastasizing BC (29). Similarly, the PCNA gene contains AP-1 binding sites in the promoter region and thus its expression is regulated by AP-1 activity (30).…”
Section: Discussionmentioning
confidence: 99%